PREVALENSI KARIES GIGI PERMANEN MOLAR PERTAMA DAN INSISIVUS PADA SISWA MIN 1 BAITURRAHMAN BANDA ACEH USIA 8-10 TAHUN - Munifah Abdat (Journal of Syiah Kuala Dentistry Society, 2018)
Dental caries is still a major problem in the child's oral cavity, generally at high risk of caries in the 8-10 year age range. Permanent dental caries can cause changes in tooth position, loss of teeth, disruption of absorption of food nutrients until the onset of infection. The purpose of this study was to determine the prevalence of caries in incisors and permanent molars in Baiturrahman MIN 1 students in Banda Aceh class IIIA and IVB. Descriptive research uses cross sectional research design with total sampling technique and obtained research subjects amounting to 81 students aged 8-10 years. Data obtained directly through DMF-T examination. The results showed high rates of caries of young permanent teeth in the incisors and first molars of 82%, of 81 students found 67 students had caries. On average 2 out of 12 young permanent teeth in one oral cavity each student aged 8 experienced caries. It was concluded that caries prevalence in incisors and permanent molars of Baiturrahman MIN 1 students was high for ages 8-10 years, there were no significant differences between male and female students, and had an impact on the emergence of new risks.Keywords: caries prevalence, incisors, first molars